Publication and the Papacy in Late Antiquity and the Middle Ages - Niskanen, Samu (Humanities, 2021)
This Element explores the papacy's engagement in authorial publishing in late antiquity and the Middle Ages. The opening discussion demonstrates that throughout the medieval period, papal involvement in the publication of new works was a phenomenon, which surged in the eleventh century. This title is also available as Open Access on Cambridge Core.